The principles of organization of academically-cognitive and self educational student`s activities on the basis of integration (Pedagogy of Higher and Secondary Education, 2013)
Bondar L. A. The principles of organization of academically-cognitive and self educational student`s activities on the basis of integration.The principles of organization of academically-cognitive and self education activities of students on the basis of integration at the university are theoretically grounded in this article. The term «principle» deals with the philosophical, psychological and educational point of view; a set of criteria which groups principles of teaching is analyzed, the system of principles of organization of the independent student`s work in the conditions of higher educational institutions is set here.
Keywords: principle; integration; self-education; academically-cognitive activity